Enantioselective Synthesis of 1, 12‐Disubstituted [4]Helicenes. (20th February 2020) - Hartung, Thierry; Machleid, Rafael; Simon, Martin; Golz, Christopher; Alcarazo, Manuel
Abstract: A highly enantioselective synthesis of 1, 12‐disubstituted [4]carbohelicenes is reported. The key step for the developed synthetic route is a Au‐catalyzed intramolecular alkyne hydroarylation, which is achieved with good to excellent regio‐ and enantioselectivity by employing TADDOL‐derived (TADDOL=α, α, α, α‐tetraaryl‐1, 3‐dioxolane‐4, 5‐dimethanol) α‐cationic phosphonites as ancillary ligands. Moreover, an appropriate design of the substrate makes the assembly of [4]helicenes of different substitution patterns possible, thus demonstrating the synthetic utility of the method. The absolute stereochemistry of the newly prepared structures was determined by X‐ray crystallography and characterization of their photophysical properties is also reported. Abstract : Minimalistisch : Die Verwendung eines chiralen Goldkatalysators mit einem α‐kationischen, von TADDOL abgeleiteten Phosphonit als Hilfsliganden ermöglicht die enantioselektive Synthese von 1, 12‐disubstituierten [4]Helicenen – eine der kleinsten helikalen Polyaren‐Architekturen.